Inverse correlation between high level expression of cyclin E and proliferation index in transitional cell carcinoma of the bladder. Issue 6 (26th November 2003) - Khan, A A; Abel, P D; Chaudhary, K S; Gulzar, Z; Stamp, G W H; Lalani, E-N
Abstract : Background/Aims: Overexpression of the G1 cyclins, D1 and E, and/or downregulation of p27 Kip1 allow uncontrolled tumour cell proliferation. This study investigated the relation between these three cell cycle proteins and tumour proliferation in bladder cancer. Method: Nuclear expression of cyclin D1, cyclin E, and p27 Kip1 was determined immunohistochemically in 52 primary transitional cell carcinomas, and the Ki-67 proliferation marker was also assessed. For each protein, the percentage of positive tumour cell nuclei was determined and analysed as a continuous variable. Results: Advancing tumour grade and pathological stage were accompanied by increasing proliferation indices, but decreasing p27 Kip1 and cyclin D1 expression, with no significant change in cyclin E expression. Overall, cyclin D1 and E expression did not correlate with proliferation. However, in cyclin D1 overexpressing tumours (⩾ 5% nuclei positive), the level of cyclin D1 expression positively correlated with proliferation. The correlation between cyclin E expression and proliferation changed from positive to negative with increasing levels of cyclin E expression, accompanied by a coordinate increase in p27 Kip1 expression. Overall, there was an inverse association between p27 Kip1 expression and proliferation. However, a subset of tumours displayed high proliferation indices despite high p27 Kip1 expression. The G1 cyclin index (sum of the level of expression of cyclins D1 and E) correlated positively with proliferation in superficial but not muscle invasive tumours. This correlation was stronger when the G1 cyclin index was adjusted for p27 Kip1 expression. Conclusion: These findings support a role for these proteins in the proliferation, differentiation, and progression of bladder transitional cell carcinomas.